PENGARUH CEO FEMALE (CF), CEO TENURE (CT), RETURN ON ASSETS (ROA), DAN FIRM RISK TERHADAP LEVERAGE PADA PERUSAHAAN SEKTOR CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2021 - Desandy Rahmawati; Kumba Digdowiseiso (ITB AAS Indonesia Surakarta, 2023)
This study aims to identify the impact of the observed variables: CEO Female (CF), CEO Tenure (CT), Return On Assets (ROA), and Firm Risk using control variables, namely Firm Size and Firm Age. The population in this study are Consumer Goods sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period in the last 6 years. The sample selection methodology used purposive sampling and 15 companies were selected as samples. Data analysis was performed using panel regression with a significance level of 0.05 using STATA 17. The results showed that the CEO Female (CF), Return On Assets (ROA) and Firm Risk CEO Tenure (CT) variables had a positive and insignificant impact on leverage. Keywords : CEO Female (CF), CEO Tenure (CT), Return On Assets (ROA), Firm Risk Leverage.